Measuring Cytoskeletal Mechanical Fluctuations and Rheology with Active Micropost Arrays. Issue 5 (25th May 2022) - Shi, Yu; Sivarajan, Shankar; Crocker, John C.; Reich, Daniel H.
Abstract: The dynamics of the cellular actomyosin cytoskeleton are crucial to many aspects of cellular function. Here, we describe techniques that employ active micropost array detectors (AMPADs) to measure cytoskeletal rheology and mechanical force fluctuations. The AMPADS are arrays of flexible poly(dimethylsiloxane) (PDMS) microposts with magnetic nanowires embedded in a subset of microposts to enable actuation of those posts via an externally applied magnetic field. Techniques are described to track the magnetic microposts' motion with nanometer precision at up to 100 video frames per second to measure the local cellular rheology at well‐defined positions. Application of these high‐precision tracking techniques to the full array of microposts in contact with a cell also enables mapping of the cytoskeletal mechanical fluctuation dynamics with high spatial and temporal resolution. This article describes (1) the fabrication of magnetic micropost arrays, (2) measurement protocols for both local rheology and cytoskeletal force fluctuation mapping, and (3) special‐purpose software routines to reduce and analyze these data. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Fabrication of magnetic micropost arrays Basic Protocol 2 : Data acquisition for cellular force fluctuations on non‐magnetic micropost arrays Basic Protocol 3 : Data acquisition for local cellular rheology measurements with magnetic microposts Basic Protocol 4 : Data reduction: determining microposts' motion Basic Protocol 5 : Data analysis: determining local rheology from magnetic microposts Basic Protocol 6 : Data analysis for force fluctuation measurements Support Protocol 1 : Fabrication of magnetic Ni nanowires by electrodeposition Support Protocol 2 : Configuring Streampix for magnetic rheology measurements